Presentation: The Andean supernatural world - Allpanchis, Revista (1970)
In this second issue, the Revista ALLPANCHIS PHUTURINQA presents five studies whose general theme is: the Andean supernatural world. The studies that are published are not only of anecdotal interest, due to the exotic nature of the ideas expressed, but also stimulate the study of the Andean religious phenomenon. The studies go without comments or explanations. Some may feel disappointed. However, opportunities for serious reflection in common should not be lacking.